2008
DOI: 10.1002/adma.200702439
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanato Tin(IV) Dichloride: An Air‐Stable, High‐Performance, n‐Type Organic Semiconductor with a High Field‐Effect Electron Mobility

Abstract: Organic thin-film transistors (OTFTs) have attracted much attention because of their potential application in low-cost, flexible, and large-area electronics. [1,2] High-performance n-type semiconductors are an essential component in OTFT applications, such as ambipolar transistors and complementary metal-oxide-semiconductor (CMOS) circuits. [3][4][5] However, although various high-performance n-type organic semiconducting materials have been reported, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…Therefore, we synthesized this 4-(perfl uorooctyl)butylamine through four steps from C 8 F 17 I as shown in Scheme 1 via the (perfl oroalkyl)alkan-1-ol [ 32 , 33 ] and the primary amine. [ 34 ] Furthermore, N , N ′ -didecyl-1,4,5,8-naphthalene tetracarboxylic Until now, many groups have been interested in the high mobility [22][23][24][25] and air-stability [26][27][28][29] of n-channel OTFTs. As a result, the mobility of n-channel OTFTs also exceeds that of a-Si TFTs.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we synthesized this 4-(perfl uorooctyl)butylamine through four steps from C 8 F 17 I as shown in Scheme 1 via the (perfl oroalkyl)alkan-1-ol [ 32 , 33 ] and the primary amine. [ 34 ] Furthermore, N , N ′ -didecyl-1,4,5,8-naphthalene tetracarboxylic Until now, many groups have been interested in the high mobility [22][23][24][25] and air-stability [26][27][28][29] of n-channel OTFTs. As a result, the mobility of n-channel OTFTs also exceeds that of a-Si TFTs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the mobility of F 16 CuPc single crystal has reached 0.35 cm 2 ·V −1 ·s −1 [25] . Song et al [26] reported phthalocyanato tin (IV) dichloride (SnCl 2 Pc) is a high performance n-type organic semiconductor for OFETs applications. An electron mobility of 0.3 cm 2 ·V −1 ·s −1 has been realized in air.…”
Section: Figurementioning
confidence: 99%
“…Here, we report $15% improvement of power conversion efficiency using phthalocyanine tin (IV) dichloride (SnCl 2 Pc), a stable n-type material with high carrier mobility and low band gap [35], as an acceptor-like cathode interfacial layer in …”
Section: Introductionmentioning
confidence: 99%